MASKER QUOTES SEBAGAI MEDIA UNTUK MENGEDUKASI MASYARAKAT MELAWAN COVID 19 - erny roesminingsih; mohammad syahidul haq; Windasari Windasari; Sri Setyowati (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2021)
The Covid-19 pandemic has increasingly spread throughout the world, so the World Health Organization (WHO) has increased the status of world health which was previously endemic to pandemic. In Indonesia, this virus has spread in all provinces. Based on the last updated data (28 May 2020), Surabaya ranks second and tends to continue to rise until now. This data shows that the spread of the virus is very massive and needs to be stopped by following the WHO protocol. The government makes efforts such as physical distancing, PSBB and other efforts. Restrictions on community activities have a major impact including in the field of education. There needs to be a solution in dealing with the spread of the Covid 19 virus in this new normal period. Schools as a center of culture are able to move people in general to care more about others and themselves through "needing to use masks". Implementation methods are tailored to the needs and objectives to be achieved in this activity. PKM activities are carried out through training on making quotes masks as an educational medium for schools and the surrounding community. The results achieved in Community Service activities are partner schools, in this case SMP 6 Ekselent Hang Tuah Surabaya, have the skills to understand the concept of a healthy school by understanding the health of oneself and others referring to WHO standards with the first activity in community activities is in service learning